Resolution of Overlapping Land Certificate Disputes in the Complete Systematic Land Registration (PTSL) in Sedayu Village, Batang Regency (Indonesian Journal of Agrarian Law, 2026)
Land is vital resource with social, economic, and legal value, thus requiring legal certainty through land registration. The Indonesian goverment has implement the Comprehensive Systematic Land Registration Program (PTSL) to accelerate land certification and provide legal protection to the public; however, overlapping land certificates remain an issue in its implementation. This study aims to analyze the factors causing overlapping land certificates and mechanism for resolving them in the implementation of the PTSL in Sedayu Village, Batang Regency.  The research method use is qualitative with an empirical juridical approach through the collection of primary data in the form of interviews and secondary data in the form of laws and regulations as well as related documents. The results of the study indicate that land certificate overlaps are caused by technical factors, namely the quality of land daata in KW 456, which has not been digitally mapped; social factors, such as miscommunication among the community regarding PTSL procedurs; and administrative factors, such as the disorganization of the Village Book C administration. Resolution efforts involve improving land data quality through remapping and data validation, optimizing public outreach, and sreamlining theh administration of the Village Book C through data updtes, digitalization, and integration with the ATR/BPN system. Consequently, comprehensive and integrated resolution measures are necessary to ensure legal certainty and prevent future land disputes.